Student’s Descriptive Text Writing In SFL Perspectives - Eko Noprianto (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Descriptive text is one of genres which is demanded be mastered by high school students in Indonesia. This requires teachers to be able to deliver it well in the classroom. However, research discovered that many teachers still have limited knowledge of how to effectively teach genres in the classroom. This qualitative case study was intended to diagnose a student’s descriptive text writing through SFL perspectives to find out what problems encountered in her text writing. It is expected that after finding the problems, the teacher could design a pedagogical plan to deal with them. The results showed that the student’s major problems in writing descriptive text lied on three aspects: the inability in adjusting the social function of the text, difficulty in writing the descriptive text with a chronological schematic structures, and the difficulty in filling the text with appropriate language features such as the use of unspecific participant. Therefore, taking everything into consideration, the researcher proposed Discovery Learning model to be used in teaching descriptive text in the classroom due to its strengths.